Chitosan enhances growth and survival rate of in vitro-cultured plantlets of banana cultivar "Grand Naine". Issue 6 (2nd November 2021) - Kandha, Laxman; Kumar, Rahul; Sethi, Santosh Kumar; Bindhani, Birendra Kumar
ABSTRACT: Banana (Musa spp.) is one of the most popular fruits consumed worldwide. Multiplication of banana through tissue culture is faced with the problem of fungal contaminations. Shrimp chitosan reportedly enhances growth in tissue-cultured plants and reduces fungal and bacterial infections during the in-vitro culture of plants. The present investigation was conducted to establish an in-vitro propagation protocol with zero fungal and bacterial contamination of cultivar 'Grand Naine' using explants from the rhizome and sucker. Different combinations of 6-benzylamino purine and indole-3-acetic acid were tested in Murashige and Skoog medium to validate the influence of phytohormones on the response of explants and regeneration of shoots and roots in it. The best response and regeneration were observed at BAP 5.0 mg/L and IAA 0.5 mg/L for the rhizome explants and BAP 4.0 mg/L and IAA 0.5 mg/L for the sucker explants. The best root formation was observed at IBA 0.8 mg/L and 1.0 mg/L for the rhizome and sucker explants, respectively. To validate the effect of shrimp chitosan on the growth of both explants, culture media was supplemented with chitosan in different concentrations. The best growth of banana explants was observed with 25 mg/L shrimp chitosan. The plantlets were hardened successfully in the greenhouse,  with a survival rate of 93% for the sucker and 91% for the rhizome explants; compared with 68% and 65% for both positive controls, respectively. The present standardized protocol should be useful for the mass production of banana, germplasm conservation and development of economically important banana cultivars. Abbreviations : BAP: 6-Benzylamino purine; CS: Chitosan; DPI: Days post inoculation; IAA: Indole-3-acetic acid; IBA: Indole-3-butyric acid; MS: Murashige and Skoog medium; MT: Metric ton; Ha: Hectare; mg/L: Milligram per liter